Posterior Placenta Accreta Spectrum Disorders: Risk Factors, Diagnostic Accuracy, and Surgical Management. Issue 4 (31st October 2021) - Palacios-Jaraquemada, José Miguel; D'Antonio, Francesco
Abstract : Abstract: Posterior placenta accreta spectrum (PAS) disorders are infrequent but potentially associated with significant maternal mortality and morbidity, especially if not diagnosed prenatally. Analysis of published literature is problematic since most experiences included only a few cases. Knowledge of the risk factors associated with posterior PAS is crucial to identifying mothers at higher risk and ask for high sensitivity studies. Ultrasound has poor diagnostic accuracy in detecting posterior PAS, while magnetic resonance imaging better delineates the posterior uterine wall. In comparison, prenatal imaging's diagnostic performance in detecting posterior PAS is significantly lower than anterior placenta invasion. Management of posterior PAS depends on several factors, including maternal hemodynamic status, available resources, clinical presentation, and invasion severity. For accreta or increta cases, a compression suture is habitually enough to perform hemostasis. Nevertheless, organ involvement habitually requires a multidisciplinary team with the assistant of a general or coloproctology surgeon. The present article aims to update the risk factors, prenatal diagnosis, and surgical management of pregnancies complicated by posterior PAS.